Framing Analysis of Edy Rahmayadi's News on MedanBisnisdaily.com - Anang Anas Azhar; Daniel Pekuwali (Budapest International Research and Critics University, 2018)
Mass media has an important role in imaging. Whether we realize it or not, the image is the result of mass media construction. The mass media can lift someone so that they become famous and supported by the community but can also bring down the person to become the most hated figure. The media constructs reality through certain points of view which are then framed or framed. In this study, the framing analysis of the Gamson and Modigliani models was used to find out how the reality or image of Edy Rahmayadi was constructed or framed by MedanBisnisdaily.com. According to Gamson, framing is a way of telling stories or clusters of organized ideas in such a way and presenting the construction of the meaning of events related to the object of a discourse. This type of research is qualitative with a constructivism paradigm. From this research, Medanbisnisdaily.com describes the image of Edy Rahmayadi as a firm, but controversial and seemingly arrogant person.